Mathematcs For Junior Secondary Schools 2 - Babalola, Ife M et al (HEBN Publishers plc, 1985)
This is accompanied guides and workbooks following the thematic approach of the pupils Books to promote better understanding.
Keywords: Juvenile literature-Mathematics-Study and teaching (Secondary)-Nigeria (English)